Pyrocarbon Interposition after Capitate Head Resection - Ferrand, Mathieu; Bellemere, Philippe (Journal of Wrist Surgery, 2013)
Background Isolated lunocapitate disease is a rare situation. It includes both capitolunate arthritis and osteonecrosis of the capitate head. The management of this pathology is not defined yet.Case Description We treated three patients by resection of the capitate head and interposition of a so-called capitolunate Pi2 implant (Tornier, BioProfile, Grenoble, France). We reported encouraging results at average follow-up of 4.8 years.Literature Review Several procedures have been reported in this indication. All suffer from lack of follow-up. Four-corner fusion seems to be the most reliable solution at the expense of wrist stiffness.Clinical Relevance case series
Keywords: capitolunate joint; osteonecrosis; pyrocarbon